KIT-13, a novel plasmalogen derivative, attenuates neuroinflammation and amplifies cognition - Hossain, Md Shamim; Mawatari, Shiro; Honsho, Masanori; Okauchi, Tatsuo; Fujino, Takehiko (Frontiers in Cell and Developmental Biology, 2024)
▪ Innovative Compound: KIT-13, a novel alkyl-type plasmalogen derivative, demonstrates superior efficacy in cellular signaling and neurogenesis compared to natural plasmalogens.▪ Neuroprotective Effects: KIT-13 significantly reduces apoptosis in neuron-like cells, showcasing its potential as a robust neuroprotective agent.▪ Cognitive Enhancement: Administration of KIT-13 in adult c57BL6J (B6) male mice led to substantial improvements in learning and memory, indicating its promise for treating cognitive impairments.▪ Neuroinflammation Reduction: KIT-13 effectively attenuates neuroinflammation, reducing pro-inflammatory cytokine expression and glial activation in the brain.▪ BDNF Stimulation: KIT-13 treatment results in heightened expression of brainderived neurotrophic factor (BDNF), which is crucial for cognitive processes and neuronal health.▪ Amyloid Beta Reduction: In neuroinflammation models, KIT-13 shows remarkable efficacy in reducing the accumulation of amyloid beta, a hallmark of Alzheimer's disease.▪ Potential Therapeutic: KIT-13's superior performance over natural plasmalogens positions it as a promising therapeutic candidate for neurodegenerative conditions like Alzheimer's disease.